Measuring student satisfaction at university level students: Evidence from university of Gujrat, Pakistan - Dilpazeer, Unbreen; Altaf, Mohsin (2017)
Purpose of this study is to measure the impact of different services and facilities offered by university on overall satisfaction of students of bachelor level.This study used the concept of service-product bundle to measure the satisfaction of students through the survey.SPSS was used to analyze the results to determine the aspects of services and facilities provided by universities to which students were satisfied.Multiple regression and correlation analysis were employed to determine the relationships between dependent and independent variables.The aspects of services and facilities which contribute significantly towards student satisfaction are lecture room facilities, facilitating goods and implicit services, while additional facilities and explicit services were the facilities which do not contribute significantly towards student satisfaction at university level.The service-product bundle concept is a reliable and valid tool or method to design a survey for measurement of student satisfaction at university level and to facilitate management of universities to determine the areas, where they need to utilize their resources for improvement to capture the perceived level of student satisfaction. Concept of service-product bundle utilization puts responsibilities strictly on the service provider, rather than the service user for questionnaire design and content.